Key decisions for a store success (Inflexion Point Magazine, 2026)
This article presents the sales projections for the years 2025 and 2026 of a store dedicated to the commercialization of tools, developed from the analysis of the time series of the data collected in the years 2022 to 2024 using forecasting methods for seasonal series, which allows to understand the importance of market trends and anticipate future demand for decision making and strategies. Secondly, an aggregate plan is proposed for the following 2 years, where efficient management is guaranteed in order to meet demand at the lowest feasible cost. Finally, the multi-product break-even point is calculated.
Keywords: Demand analysis; Aggregate production plan; Company; Profit